Comparative Study of Ijtihad Methods Between Ahlussunnah and Syiah - Nirhamna Hanif Fadillah; Amir Reza Kusuma; Rofiqul Anwar Anwar (Universitas Darussalam Gontor, 2022)
This article discusses the fundamental differences in the adoption of religious law on both sides of both Ahlusunnah (Sunni) and Shiah. The two schools always reach the conclusion that the majority of Indonesia is a Sunni school of thought. Ahlusunnah itself is in the Akidah stage through stages which include prioritizing the Qur'an, Hadith, Ijma and Qiyas. While the problem of Akidah in Shiah teachings greatly affects their methodology in ijtihad, among others: first, rejecting rational principles in understanding the texts of the Qur'an and Sunnah and Shiah itself mentions that those who do not have ijtihad qualifications are required to follow the mujtahids called as marja‟al-taqlid. Second, Shia scholars understand Ijma' as a statement by a group of people who express the opinion of Imam Infallible. Third, the Shia reject the use of qiyas because they adhere to the (uncertain) dzanni proposition. Fourth, the concept of Imamah (leadership of twelve infallible Imams) and Territory, Shiah views the laws produced through the Imams as qath'i (definite) and the same as revealed texts.